2004
DOI: 10.1524/ract.92.9.559.54996
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the complex formation of metal ions with humic acids

Abstract: Based on the conceptual model of cation-humic interactions considering the heterogeneous composition and polyelectrolyte nature of humic acids, the description of the interaction by the expression, logis the concentration of the cation bound to the humic acid, [M] is the concentration of the free cation with charge z, and [R] is the concentration of the free anionic sites of the humic acid, [R] = (C R − z[M · ·(zR)])α (C R is a total concentration of proton exchanging sites and α is a degree of dissociation). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This variation is consistent with previous studies on Eu-HA complexation Kubota et al, 2002 *Stookey (1970); ** Kim et al (1990). Purification procedure of Aldrich humic acid (AHA) was followed Kim et al (1990) Tochiyama et al, 2004). In the case of the multi-REE system, however, logβ M-HS of some LREEs (La, Pr, and Nd) increase with the REE loading level at the lower REE loading region (Fig.…”
Section: Iron and Al In Hasupporting
confidence: 89%
See 3 more Smart Citations
“…This variation is consistent with previous studies on Eu-HA complexation Kubota et al, 2002 *Stookey (1970); ** Kim et al (1990). Purification procedure of Aldrich humic acid (AHA) was followed Kim et al (1990) Tochiyama et al, 2004). In the case of the multi-REE system, however, logβ M-HS of some LREEs (La, Pr, and Nd) increase with the REE loading level at the lower REE loading region (Fig.…”
Section: Iron and Al In Hasupporting
confidence: 89%
“…Some experimental studies on Eu-HA interaction indicated that the apparent binding constant of Eu with HA depends on the Eu loading level to HA Kubota et al, 2002;Tochiyama et al, 2004). Hummel et al (2000) demonstrated that the experimental binding constants of Eu-HA complexes, which were reported by Caceci (1985) and Glaus et al (2000), decrease with an increase in the Eu loading level.…”
Section: Fig 1 Ree Patterns Of Logk Ma For Ha (A) Leonardite Coal mentioning
confidence: 91%
See 2 more Smart Citations
“…where m i , b, and logK i are the characteristic constant parameters of the humic substance [28]. At a given I, the [R -] is defined by the sum of two dissociated functional groups of the humic substance (R -) in meq/g, where j g of the humic substance is dissolved in V dm 3 of the solution,…”
mentioning
confidence: 99%